Defect in Synaptic Vesicle Precursor Transport and Neuronal Cell Death in KIF1A Motor Protein–deficient Mice - Yonekawa, Yoshiaki (The Rockefeller University Press, 1998)
The nerve axon is a good model system for studying the molecular mechanism of organelle transport in cells. Recently, the new kinesin superfamily proteins (KIFs) have been identified as candidate motor proteins involved in organelle transport. Among them KIF1A, a murine homologue of unc-104 gene of Caenorhabditis elegans, is a unique monomeric neuron– specific microtubule plus end–directed motor and has been proposed as a transporter of synaptic vesicle precursors (Okada, Y., H. Yamazaki, Y. Sekine-Aizawa, and N. Hirokawa. 1995. Cell. 81:769–780). To elucidate the function of KIF1A in vivo, we disrupted the KIF1A gene in mice. KIF1A mutants died mostly within a day after birth showing motor and sensory disturbances. In the nervous systems of these mutants, the transport of synaptic vesicle precursors showed a specific and significant decrease. Consequently, synaptic vesicle density decreased dramatically, and clusters of clear small vesicles accumulated in the cell bodies. Furthermore, marked neuronal degeneration and death occurred both in KIF1A mutant mice and in cultures of mutant neurons. The neuronal death in cultures was blocked by coculture with wild-type neurons or exposure to a low concentration of glutamate. These results in cultures suggested that the mutant neurons might not sufficiently receive afferent stimulation, such as neuronal contacts or neurotransmission, resulting in cell death. Thus, our results demonstrate that KIF1A transports a synaptic vesicle precursor and that KIF1A-mediated axonal transport plays a critical role in viability, maintenance, and function of neurons, particularly mature neurons.